Effectiveness of Mathematical Modules with Guided Discovery Approach Viewed from PGSD UAD Student Motivation and Achievement - A Mardati (Pascasarjana Universitas Pendidikan Indonesia, 2020)
The aim of the study was to determine the effectiveness of product development in the form of mathematical modules with a guided discovery approach in terms of motivation and learning achievement of UAD PGSD students. Guided discovery approach is a method that involves students in an optimum way to find formulas and theorems, while educators provide guidance to students who have difficulty. This type of research is a quasi-experimental study with pretest-posttest nonequivalent comparison-group design. The group used in this study consisted of two groups, namely the experimental group and the control group. Based on the calculation in the attachment, the value of t count is 5.37. The calculated t value obtained is greater than ttable = t0.05; 28 = 1.701 so Ho is rejected. Thus it can be concluded that at the 5% significance level, approach is the guided discovery effective in terms of student learning achievement. Based on the calculation in the attachment, the value of t count is -1.805. The calculated t value obtained is smaller than ttable = 1.701 so Ho is not rejected. Thus it can be concluded that at the 5% significance level, approach is the guided discovery not effective in terms of student learning motivation. It can be concluded that mathematics learning with a guided discovery approach is effective in terms of student learning achievement, but is not effective in terms of student learning motivation.